The historiographical debate about the 14th century crisis: between the great depression and the development of the modern world - Michelan, Katia Brasilino [UNESP] (Univ Passo Fundo, 2024)
The aim of this article is to examine how the 14( th) century has been understood by European historiography that has delved into this period. To achieve this, we will juxtapose economic, political, social, and cultural perspectives of analyses that sought to consider the 14 (th) century as a period of crises that culminated in the end of the Middle Ages and the beginning of the Modern Age, with the emergence of capitalism. Alternatively, these analyses questioned the notion of crisis and shed light on the period's advancements while emphasizing continuities and persistences. Without claiming to exhaust the debate, the intention here is to demonstrate the interpretative possibilities and historiographical revisions concerning a historical period seen as fundamental for the analysis of the Western world.
Keywords: Historiography; Middle Ages; 14( th) Century Crisis